2008
DOI: 10.1143/jjap.47.4111
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sonoluminescence and Bubble Dynamics using Pulsed Ultrasound at 103 kHz

Abstract: Enhancement of multibubble sonoluminescence was observed for pulsed ultrasound at 103 kHz. High-speed photography was also used to obtain the images of cavitation bubbles at a frame rate of 150,000 fps in continuous wave mode and pulsed wave mode. Most bubbles oscillated spherically and showed frequent coalescence in continuous wave mode at an applied voltage of 28 Vpp. The maximum bubble radius was measured to be 20–30 µm. Only in pulsed wave mode the following complex structure of bubble oscillation was capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The pulsed ultrasound may prevent the production of large degassing bubbles which absorb ultrasound energy, resulting in the increase in the active bubble population. Choi et al [34] also reported the acoustic emission spectra, showing that subharmonic components and broadband Fig. 9 The size distributions of SCL-emitting bubble at 213, 355, 647, 875, 1056, and 1136 kHz obtained using a pulsed ultrasound.…”
Section: Size Distribution Of Sonoluminescence Bubblesmentioning
confidence: 94%
See 1 more Smart Citation
“…The pulsed ultrasound may prevent the production of large degassing bubbles which absorb ultrasound energy, resulting in the increase in the active bubble population. Choi et al [34] also reported the acoustic emission spectra, showing that subharmonic components and broadband Fig. 9 The size distributions of SCL-emitting bubble at 213, 355, 647, 875, 1056, and 1136 kHz obtained using a pulsed ultrasound.…”
Section: Size Distribution Of Sonoluminescence Bubblesmentioning
confidence: 94%
“…In a pulsed ultrasound experiment, the enhancement of SL intensity or OH radical production may occur by an appropriate choice of pulse on-time and pulse off-time. Choi et al [34] reported the enhancement of SL intensity and acoustic emission spectra at 103 kHz. As shown in Fig.…”
Section: Size Distribution Of Sonoluminescence Bubblesmentioning
confidence: 99%
“…A different insight into pulse sonication induced enhancement was provided by Choi et al [65]. They reported that bubbles that survive during the pulse off time were able to grow by the subsequent pulse to a size larger than that reached in continuous mode.…”
Section: Sonoluminescence and Sonochemiluminescencementioning
confidence: 98%
“…This effect was explained in terms of a "cascade" effect where bubbles generated during the acoustic pulse on time survive through the shorter pulse intervals and thus act as further cavitation nuclei for the subsequent pulse. This effect was captured using a high speed camera by Choi et al [65]. dissolve away before the subsequent pulse arrives and decrease the effective population of cavitation nuclei available to be grown to the active size during the pulse on time and effectively lower the overall cavitation activity.…”
Section: Sonoluminescence and Sonochemiluminescencementioning
confidence: 99%
See 1 more Smart Citation